Intel Galileo Essentials. - Grimmett, Richard (Packt Publishing, 2015)
Intel Galileo Essentials provides step-by-step instructions on how to use the Galileo in Do-It-Yourself electronics projects. We begin by powering up the Galileo and loading the development system to get started. Post this, we look at GPIO capability in general along with the basics of programming the GPIO pins, also learning how to connect external HW to the GPIO pins. Moving on, we begin connecting a display to the Galileo, while learning the important points such as importing the support files, programming text and graphics, and getting input from a touchscreen. More significantly, we start controlling motors, adding sensors, and learning how to communicate wirelessly with your Galileo projects. We conclude by building a wide variety of projects with the Galileo such as controlling servos for walking robots, hacking toy robots with the Galileo, and creating an ROV (Remotely Operated Vehicle) with the Galileo.